Uganda: Cost effective options for inclusive and sustainable development - Aragie, Emerta A.; Thurlow, James; Ahmed, Hashim; Jones, Eleanor (International Food Policy Research Institute, 2025)
In this policy brief, we present findings of a systematic evaluation and ranking of investment options for Uganda’s agrifood system based on their cost-effectiveness in achieving multiple development outcomes, including agrifood gross domestic product (GDP) growth, agrifood job creation, poverty reduction, declining rates of undernourishment, and lowering diet deprivation. Additionally, the study assesses their impact on environmental footprints, focusing on water consumption, land use, and emissions. Investments in small and medium enterprise (SME) processors are shown to be the most cost-effective at expanding agrifood GDP and employment, while livestock extension services rank highest among the farmer-facing investments. Most R&D related interventions rank lowest in terms of cost-effectiveness at achieving economic and social outcomes. However, many cost-effec tive investments have relatively high environmental footprints, highlighting tradeoffs. The study further reveals shifts in the cost-effectiveness ranking of investment options over time and when ex treme production shocks occur.